2011
DOI: 10.1080/14662043.2011.582731
|View full text |Cite
|
Sign up to set email alerts
|

Patrimonialism and neopatrimonialism: comparative trajectories and readings

Abstract: accessible en ligne : http://dx.doi.org/10.1080/14662043.2011.582731International audienceThere is a striking contrast between the dissemination of the concept of neopatrimonial rule in Africa and its more parsimonious mobilisation outside the continent. The increasing assimilation of the African neopatrimonial state to integral and predatory forms of politics has contributed to its perception as a global prototype of the 'anti-developmental' state. The article contrasts this trajectory with those observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(51 citation statements)
references
References 43 publications
0
48
0
3
Order By: Relevance
“…As a number of pieces have persuasively argued, the concept is deployed so broadly that it tends to cloud the large variation in economic and political outcomes across the continent (Pitcher et al, 2009;Bach, 2011;Mkandawire, 2015;Crook, 1989;Theobald, 1982). Contrary to the dominant perspectives, these works show how neopatrimonialism can be a force for democracy, social cohesion, redistribution, administrative effectiveness and development.…”
Section: Democracy With One Adjectivementioning
confidence: 99%
“…As a number of pieces have persuasively argued, the concept is deployed so broadly that it tends to cloud the large variation in economic and political outcomes across the continent (Pitcher et al, 2009;Bach, 2011;Mkandawire, 2015;Crook, 1989;Theobald, 1982). Contrary to the dominant perspectives, these works show how neopatrimonialism can be a force for democracy, social cohesion, redistribution, administrative effectiveness and development.…”
Section: Democracy With One Adjectivementioning
confidence: 99%
“…Studies forwarding a neopatrimonial thesis to explain Africa's stunted political and economic development have portrayed the continent as captive to interests that privatised the state. The political leadership in vogue has been described in various ways: personalism, clientelism, big man, tyrants, autocrats, patronage and neopatrimonialism (Bach, 2011;Bratton & van de Walle, 1997;Erdmann & Engel, 2007;Jackson & Rosberg, 1982;Pitcher, Moran, & Johnstone, 2009). While neopatrimonialism has acquired greater popularity in the literature, it has also been the most contested in terms of both its meaning and effect (deGrassi, 2008;Pitcher et al, 2009).…”
Section: The Challenge Of the Neopatrimonial Paradigmmentioning
confidence: 97%
“…So where then was the room for ethnic influence in public policy that stalled development? The development impasse was a factor of (mis)calculations the leaders made, not ethnic competition (Bach, 2011;Pitcher et al, 2009). Thus, if neopatrimonialism defined African polities, then the African development impasse cannot at the same time be attributed to lack of consensus resulting from ethnic diversity.…”
Section: The Challenge Of the Neopatrimonial Paradigmmentioning
confidence: 98%
“…Social psychologists have shown that when people are exposed to a prolonged culture of violence and armed conflict, they are left with a twisted worldview that tends to perceive use of violence, aggressive behavior and resort to disorder as a normal way of life (Kelman 2010). Many studies have shown how virulent patterns of neopatrimonial politics have at different conjunctures produced or reinforced the culture of political violence in the African fragile, weak, failed and collapsed states (Rotberg 2004;Bach 2011;Ewusi 2014). Abu Bakarr Bah (2011) has specifically used the example of Sierra Leone to show how the processes of state decay, marked by the systematic deterioration of the state's capacity to deliver positive political goods, could precipitate a descent to war and feed a culture of violence.…”
Section: The Structural Impediments To Peace and Conflict-sensitmentioning
confidence: 99%